Influence of natural-geographical and historical-social conditions on lawmaking (Journal of actual problems of jurisprudence, 2018)
In article are considered questions of influence of objective factors on lawmaking, communication of legislative activity with public conditions and their interdependence. The basic types of objective factors that influence the law-making, the formation of the text of the law is natural-geographical and social-historical bases. In article discusses the essences of natural-geographical and social-historical conditions, their value, need to consider them in the process of lawmaking, and also are analyzed extent of influence of these factors on lawmaking of the country.Key words: Parliament, law, legislative activity, legislator, deputy, society, objective factor, social-historical and natural-geographical conditions, culture, mentality, traditions.